Managerial ability of the management influence on employee performance of the republic of Indonesia employee cooperative (KPRI) Pengayoman City Makassar - Romansyah Sahabuddin; Deddy Ibrahim Rauf; Raissa Muhayminah Arimansah Putri; Lutfillah Nursadrina S; Lutfin Mufida; A. Dara Nurfadilah; Ahmad Rifani (Trigin Publisher, 2023)
The mission of this research was to determine the ability of management in influencing employee performance at the Republic of Indonesia Employee Cooperative (KPRI) Pengayoman Makassar City. This research variable has an independent variable, namely the management ability of the board (X1) and the dependent variable, namely employee performance (Y). This study method uses descriptive analysis with a quantitative approach and descriptive research includes data collection to test hypotheses and use statistical tests. Based on the results of the study, a simple linear regression equation = 9.949 + 0.889 (X) was obtained. The results of the simultaneous test state that the simultaneous count is = 83.278 and significant = 0.000 <0.05, which means that the hypothesis: